TINGKAT PENCEMARAN WADUK PENJALIN KECAMATAN PAGUYANGAN KABUPATEN BREBES DITINJAU DARI STRUKTUR KOMUNITAS PLANKTON - Octyviana Arum; Agatha Sih Piranti; Christiani Christiani (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
Penjalin Reservoir is located in Brebes Regency, Indonesia. Human activity around Penjalin Reservoir, such as irrigation, aquaculture, and sanitation can affect its water’s quality. Plankton can be used as bioindicator since its existence is heavily affected by water physical and chemical factors. Polluted waters can affect diversity and abundance of plankton. The purpose of this research were to determine waters quality of Penjalin Reservoir, to know plankton community structure (abundance, diversity, and domination), and pollution level of each sampling station based on plankton diversity. This research used survey method on 6 sampling stations covering inlet, middle of reservoir, and outlet with 3 replicates and 4 weeks interval. Water quality were analyzed descriptively based on criteria of PP No. 82 Tahun 2001. Abundance and diversity were estimated as Shanon-Wiener index. Domination were estimated as Simpson index. Plankton abundance values varies from 4,970.30 to 12,923.37 ind/l with the most abundant species was Tetraedon minimum. Diversity index (H’) were high with value around 3.28–3.55 and domination index were around 0.04–0.07. These diversity indexes showed that the water quality of Penjalin Reservoir were not polluted.